2002
DOI: 10.1002/1521-3773(20020703)41:13<2403::aid-anie2403>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

A New Highly Efficient Ruthenium Metathesis Catalyst This work was supported by the Fonds der Chemischen Industrie.

Abstract: Catalytic olefin metathesis has recently become a powerful tool for carbon-carbon-bond formation in organic chemistry. [1] Over the last three years it has been demonstrated that ruthenium alkylidenes that bear N-heterocyclic carbene ligands, for example, 1 and similar analogues, exhibit extraordinary activity and stability. [2] Studies on the mechanism of olefin metathesis reactions have also been described. [2e,f] Phosphane-free catalyst 2 [3] has also recently been developed and studied. This catalyst … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
99
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 285 publications
(102 citation statements)
references
References 22 publications
3
99
0
Order By: Relevance
“…1 H NMR (500 MHz, CDCl 3 ) δ 10.53 (d, J = 0.8 Hz, 1H), 7.85 (dd, J 1 = 7.7 Hz, J 2 = 1.8 Hz, 1H), 7.55 (ddd, J 1 = 8.4 Hz, J 2 = 7.3 Hz, J 3 = 1.8 Hz, 1H), 7.09-7.04 (m, 1H), 6.98-6.95 (m, 1H), 4.36 (t, J = 5.7 Hz, 2H), 3 …”
Section: 79%mentioning
confidence: 99%
See 1 more Smart Citation
“…1 H NMR (500 MHz, CDCl 3 ) δ 10.53 (d, J = 0.8 Hz, 1H), 7.85 (dd, J 1 = 7.7 Hz, J 2 = 1.8 Hz, 1H), 7.55 (ddd, J 1 = 8.4 Hz, J 2 = 7.3 Hz, J 3 = 1.8 Hz, 1H), 7.09-7.04 (m, 1H), 6.98-6.95 (m, 1H), 4.36 (t, J = 5.7 Hz, 2H), 3 …”
Section: 79%mentioning
confidence: 99%
“…Analytical data were in agreement with published data. 3 In our hands, it was found that the title compound decomposed rapidly in solution in solvents that were not rigorously dried and degassed. Thus, when using Method A, all manipulations were performed in the glovebox.…”
Section: Blechert Catalyst (5)mentioning
confidence: 99%
“…Initiation of C40 itself is slow, despite the low oxophilicity of Ru(II), owing to the high thermodynamic stability of the five-membered chelate ring. Improved turnon efficiency was achieved by steric (C41 [133,134]) or electronic (C42 [109,110,135]) destabilization of the chelate.…”
Section: Catalysts That Converge On Rucl 2 (Nhc)(ch 2 )mentioning
confidence: 99%
“…Substrates bearing terminal olefins were rapidly cyclized to five-to sevenmembered rings under mild conditions (0-23 ˚C, 1 mol % Ru) [109,110,[133][134][135]; slightly greater activity was generally manifested by C41b [110]. The substrates shown in Scheme 19 proved more challenging.…”
Section: Catalysts That Converge On Rucl 2 (Nhc)(ch 2 )mentioning
confidence: 99%
“…A N-heterocyclic carbene ligand containing a binaphthyl substituent induces excellent enantioselectivity for some ring-opening/cross metathesis reactions in air, 167 and a functionalised alkylidene incorporating a hemilabile ether moiety has been investigated for ring closing metathesis. 168 A DFT study on the mechanism of olefin metathesis using ruthenium() N-heterocyclic carbene complexes has also been investigated. 169 In related chemistry a very rare example of a terminal carbide ligand has been isolated originating from a unique carbon atom transfer reaction as shown in Scheme 2.…”
Section: Iron Ruthenium Osmiummentioning
confidence: 99%